Analyzing of global mapping research trends on firefly tourism and fireflies (Coleoptera: Lampyridae) from the year 2000 – 2022: a literature review and bibliometric analysis - Muhammad Fakruhayat Ab Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Fireflies are very attractive insects that have obtained a lot of attention from nature tourists in recent years and firefly tourism has the potential to bring in a lot of income for local communities, states, regions, and even countries. Therefore, this study presents a literature review and bibliometric analysis of firefly tourism and fireflies Coleoptera Lampyridae research around the world from 2000 to 2022 to provide researchers and scholars around the world with a visualization or analyzing of the global mapping research trends results using RStudio 4.2.0 and Biblioshiny. A textual query on two databases; Scopus (643 articles), and Web of Science (78 articles) was performed on 12 June 2022 retrieving 721 scholarly articles from 2000 to 2022 for in-depth analysis. According to the findings of the analysis, there is a significant inconsistency of global trends in annual scientific production, with the number of publications increasing and decreasing. The United States of America (USA) has the highest number of scientific productions, as the most relevant author is Viviani VR (Scopus) and Lewis SM in Web of Science (WoS) database, while the most relevant journal is Zootaxa in Scopus and Web of Science database, and the most frequent word is “bioluminescence” in Scopus database but the word “Lampyridae” is the most used word in the Web of Science database. USA with Japan and China have the highest collaboration among other countries in this field of research topic.